Effect of Different Diets on Biology of Corcyra Cephalonica (Stainton) under Laboratory Condition in Chitwan, Nepal - Bhandari, Gopal; Regmi, Rajendra; Shrestha, Jiban (International Journal of Applied Sciences and Biotechnology, 2014)
The experiments were conducted from 10th October, 2013 to 10th January, 2014 in Entomology Laboratory of National Maize Research Program, Rampur, Chitwan, Nepal at 26±2ºC and 70±5% RH in order to assess diet performance on the biological parameters of Corcyra cephalonica (Stainton). Four cereals namely corn, rice, millet and wheat were tested solely and mixed with groundnut. Among the eight treatments, corn + groundnut was superior diet in almost biological parameters of C. cephalonica followed by millet + groundnut. The experiment showed that the corn + groundnut are biologically better option for production of robust eggs of C. cephalonica. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11587Int J Appl Sci Biotechnol, Vol. 2(4): 585-588